1998
DOI: 10.1007/s004200050268
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to lead and other metals in children from Katowice district, Poland

Abstract: In all, 7% of the Polish children had blood lead levels exceeding 0.5 mumol/l, the concentration above which negative effects on mental development have been reported. However, the findings indicate a decrease in lead exposure during recent years among the Bytom children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Previous biological monitoring surveys in the Katowice industrial region of Poland (Zejda and Grabecki, 1994;Osman et al, 1998) revealed lead exposure levels in school children similar to those reported to cause alternations in auditory functions. The purpose of the present study was to evaluate if hearing impairments from lead exposure do occur in children in the Katowice region.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…Previous biological monitoring surveys in the Katowice industrial region of Poland (Zejda and Grabecki, 1994;Osman et al, 1998) revealed lead exposure levels in school children similar to those reported to cause alternations in auditory functions. The purpose of the present study was to evaluate if hearing impairments from lead exposure do occur in children in the Katowice region.…”
Section: Introductionsupporting
confidence: 59%
“…Second, a peak in blood lead at about 2 years of age has been observed (Baghurst et al, 1992). It should also be noted that the lead pollution in the Katowice area has decreased, resulting in a trend of decreasing blood lead levels (Osman et al, 1998). In fact, the average blood lead concentration in the current study group was only about half of that obtained 1 to 3 years earlier, and the fraction of children with blood lead above 150 g/L (0.72 mol/L) was one-fourth that of the studies used for the selection of the children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, particularly children, low dietary intakes of iron, zinc, and calcium have been associated with increased BLLs [36,37]. Lead that is swallowed at fasting is absorbed to a high level as compared to the condition with ingested food.…”
Section: Resultsmentioning
confidence: 99%